Influence of Censorship on the Minimax Risk of Decision Procedures - Kałuszka, Marek (Statistics (Berlin, DDR), 1997)
Gajek and Gather(1991) showed that under the presence of censoring a trivial estimator of the scale parameter not depending on the sample can be both minimax and admissible. We consider a general decision problem. No assumptions are imposed on decision space, decision procedures and loss function except standard ones. It is shown that the anomaly also occurs. Some related results are given.